Biophysical assessments and blood profiling reveal physiological adaptations and environmental interactions of hilsa shad (Tenualosa ilisha) - Saeed Anwar; Abdul Kader; Smrity Kona Debnath; Faria Jarin; Abu Saleh Mohammad Sayem; Md. Faruque Miah (PLoS ONE, 2025)
The hilsa shad (Tenualosa ilisha) is a migratory fish of great economic and cultural importance in Bangladesh. However, its physiological adaptations to diverse environmental conditions are not well understood. This study provides a comprehensive assessment of the biophysical, hematological, and biochemical characteristics of hilsa shad from riverine, estuarine, and marine environments in Bangladesh. We sampled 180 adult fish from nine sites, revealing significant habitat-specific variations in water quality, with marine sites showing the highest levels of total dissolved solids (TDS) and specific conductance. Hematological analysis showed that fish from riverine environments had higher hematocrit values, which are crucial for oxygen transport during migration. Post-spawning fish exhibited elevated hemoglobin, RBC counts, and hematocrit levels, reflecting adaptations to the metabolic demands of migration and spawning. WBC counts were higher in females, particularly in estuarine and marine environments, suggesting a stronger immune response to environmental stressors. Serum biochemical analysis showed significant variations in liver enzyme activity, albumin, and cortisol levels, with elevated cortisol in riverine fish during spawning season, indicating heightened stress. These findings enhance our understanding of hilsa shad’s physiological ecology, providing critical insights for conservation and management strategies amid environmental changes.